Structural Equation Modeling Approach To Shaping Of Differences In Private Label Adoption In Groceries Segment - Tandon, Nidhi; Verma, Jayender (The journal of contemporary issues in business and government, 2021)
The research is needed more across “consumer” correlates than the “manufacturer” and “retailer” based correlates as these constitute the most significant aspects that could probably shape the market shares and success of branding across multi- tier private labels being promoted by organized food retailers. Store based offering of diverse food product categories (spices, grains, flours, ingredients, pulses, refined oils and cooking medium, tea and beverages, commodiments) seem to have brought the retailer in direct competition with manufacturer brand. In this regard the research leverages the structural equation modeling approach to ascertain the differences in propensity to adopt private labels on account of changes in grocery nature (pulses, spices, dairy, snack, oil, grain). The research study relied on Likert scale based pre validated scales to operationalize the factors. The sample size of 600 was undertaken with a valid sample size of 438. Across grocery segments, contrasting observations were reported. The impact of product attributes, consumer psychographics, store efforts and restraining forces was evident in varying proportions.Contribution: The research findings promote the earlier studies under the umbrella of „cue utilization‟ theory, „planned behavioral‟ prospects, „expected utility‟ prospects and „self-perception‟ theory. In terms of knowledge creation, the outcomes extend the resource-based theory and behavioral basis of marketing in retailing arena. In terms of theoretical consequences, the research outcomes reflect the incidence of impact of positional strategies as key to competitiveness on day to day basis.